Theology of Culture in Muslim Southeast Asia - Azhar Ibrahim (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2022)
Theology of culture is essentially multi-disciplinary in its foundation where it should be able to appropriate discursive theology, sociology, philosophy, history, psychology etc. Theology of culture cannot be simply an exercise of appropriating the scriptural injunctions. In the history of the dissemination of Islam in this part of this world, the cultural role is instrumental in the process of Islamisation. Understanding the religious life and discourse in this region will not be completed if the realm and significance of culture is being relegated. It is imperative for Muslims in Southeast Asia to develop theology of culture as part of their intellectual and religious discourse, nourishing them with the notion of dialogue, criticality and reconstruction. In more specific term, the need to garner the interest on culture is important where student of religion could engage, like other students of culture, by giving critical religious perspectives, on a domain that affect their life and humanity as a whole. Our cultural and intellectual responses to the predicaments of our time are urgently needed, especially when the political responses always beset by more problems and confusion. To attempt an alternative approach must be recognized and made available. Herein lies the importance of a theology of culture.